Conflicts of Interest in the Underwriting of IPOs and Price Stabilization - De Carvalho, Antonio Gledson (2015)
Banks that supply capital and simultaneously underwrite securities for the same clients may benefit themselves or their clients at the expenses of investors by overpricing securities. We investigate this issue by analyzing price stabilization and short-term returns of IPOs. Our analysis suggests that equity-conflicted underwriters overprice IPOs and use price stabilization to disguise overpricing. The same does not happen with loan conflicted underwriters. We also show that the partial adjustment phenomenon may result from price stabilization, since it disappears after the stabilization is over.